Natural Caffeic Acid‐Based Polyphenol‐Form Polymer as Self‐Therapeutic Drug Carrier Uniquely Targeting and Sensitizing Chemotherapy of Triple‐Negative Breast Cancer - Chen, Lezong; Dai, Chunlei; Wang, Liying; You, Xinru; Wu, Jun; Song, Yuanbin; Xu, Jingbo (Small structures, 2025)
Drug carriers constructed from natural plant‐derived bioactive molecules, such as polyphenols, not only provide a new strategy to enhance the drug therapy efficacy but also help bring sustainability concept to pharmaceutical industry. Here, the natural caffeic acid into polyphenol‐form polymer with free pendant phenolic hydroxyl groups (Ph‐CaA‐OH) is prepared by one step, simple, and mild polycondensation method, then it is utilized as a self‐therapeutic drug carrier against triple‐negative breast cancer (TNBC). The Ph‐CaA‐OH can self‐assemble into sub‐100 nm nanoparticles (PCOH NPs) and exhibit unique dose‐dependent cytotoxicity to TNBC cell lines, promoting intracellular reactive oxygen species production and causing DNA double‐strand break damage. Moreover, PCOH NPs regulate the expression of Vimentin, ZEB‐1, and E‐cadherin to inhibit the epithelial‐mesenchymal transition progression of TNBC cells. The experimental results in vivo indicates that PCOH NPs could highly penetrate and accumulate inside the tumor, and both PCOH NPs and paclitaxel‐loaded PCOH NPs show stronger tumor suppressive effects than paclitaxel and Abraxane without significant side effects. This newly developed Ph‐CaA‐OH works excellent as a therapeutic nanodelivery platform with specific self‐anti‐TNBC activity and TNBC targeting capability, providing a new strategy for therapy of TNBC and other tumors, plus expanding the applications of polymerized caffeic acid‐based biomaterials.